2020
DOI: 10.1161/cir.0000000000000768
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving for Individuals With Heart Failure: A Scientific Statement From the American Heart Association

Abstract: Many individuals living with heart failure (HF) rely on unpaid support from their partners, family members, friends, or neighbors as caregivers to help manage their chronic disease. Given the advancements in treatments and devices for patients with HF, caregiving responsibilities have expanded in recent decades to include more intensive care for increasingly precarious patients with HF—tasks that would previously have been undertaken by healthcare professionals in clinical settings. The specific tasks of careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
195
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(210 citation statements)
references
References 48 publications
7
195
0
8
Order By: Relevance
“…This is important because before this study, it was assumed that some baseline physical limitations of the patients could be related more to age or muscular or neurological disorders rather than to HF symptoms, but surprisingly, most of them experienced a better physical situation, something that could be related to the better perception in their QoL emotional domains. Depression and anxiety are not systematically studied in patients with HF, but they are very important components of QoL [21,22]. Dereli et al [23] have demonstrated a significant positive effect of sacubitril/valsartan on different depression and anxiety parameters in patients with HF and a reduced LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because before this study, it was assumed that some baseline physical limitations of the patients could be related more to age or muscular or neurological disorders rather than to HF symptoms, but surprisingly, most of them experienced a better physical situation, something that could be related to the better perception in their QoL emotional domains. Depression and anxiety are not systematically studied in patients with HF, but they are very important components of QoL [21,22]. Dereli et al [23] have demonstrated a significant positive effect of sacubitril/valsartan on different depression and anxiety parameters in patients with HF and a reduced LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…While informal caregivers are at increased risk for worse physical and mental health (Kitko et al, 2020), the precise relationship between self-care and adverse caregiver outcomes have not been extensively examined in HF. However, our findings suggest that caregivers at risk for poor self-care may also be susceptible to other negative caregiver outcomes, particularly higher levels of caregiver burden and more depression.…”
Section: Self-care Classes Caregiver Burden and Depressionmentioning
confidence: 99%
“…In fact, around 43.5 million caregivers report providing care at home within the last 12 months (National Alliance for Caregiving (NAC) and the AARP Public Policy Institute, 2015), with caregivers carrying out activities previously performed by trained clinicians (Kitko et al, 2020). This trend is expected to increase in HF caregivers due to a rapidly aging U.S. population and subsequent rise in HF incidence (Vigen et al, 2012).Caregivers play an integral role in HF patient self-care (Kitko et al, 2020) and are involved in day-to-day disease management activities including monitoring and treating symptoms, managing medications, providing emotional support, assisting with daily activities, and providing transportation (Kitko et al, 2020;Riegel et al, 2017). Caregivers perform these activities while maintaining personal responsibilities, such as employment and family obligations (Dionne-Odom, Hooker, et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers of adults living with heart failure (HF) experience many of the same issues as caregivers of adults with other illnesses and conditions. HF patients often have other chronic conditions resulting in complex care regimens that can complicate caregiving (Kitko et al, 2020). The natural disease course for a person with HF is highly variable with a decline in function over a period of time that may be long (Virani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%